Exploring Key Drivers of Tourist Satisfaction in Sawah Lukis Agritourism Using SEM-PLS Approach - Dian Retno Intan; Khairul Fahmi Purba; Juita Rahmadani Manik; M. Alfi Syawlis; Wildani Lubis; Nana Trisna Mei Br Kabeakan (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2025)
Agritourism is becoming increasingly popular in Indonesia as it utilizes natural resources and agricultural potentials, such as natural landscape and rural culture, as its main attractions. North Sumatra Province has iconic tourist attractions, such as Lake Toba, Sipiso Piso waterfall, and Agritourism, such as Sidamanik Tea plantation, Berastagi Botanical Garden and Sawah Lukis agritourism in Binjai. Sawah Lukis Agritourism has experienced a significant increase in tourist visits. Due to the high competition in Agritourism, the management should accommodate tourist expectations to achieve tourist satisfaction. Tourists' satisfaction is influenced by tourism attraction and service quality. This research explores and investigates the key drivers of tourist satisfaction in Sawah Lukis Agritourism. Accidental sampling was employed to select 102 visitors of Sawah Lukis Agritourism. Data was gathered from October to December 2024. Variables measured were tourist attractions and service quality as the exogenous variables and tourist satisfaction as the endogenous variable. The exogenous variables had 29 measurement indicators, and the endogenous variable had six measurement indicators. Data analysis was performed using SEM-PLS (Structural Equation Model - Partial Least Square) assisted by WarpPLS 7.0 software. The result showed that the constructed model was fit and fulfilled the outer and inner model criteria. The findings of this study indicate that all the key variables, which were tourism attraction and service quality, were key-driven and had a positive significant influence on the tourist satisfaction of Sawah Lukis Agritourism. The enhancement of tourist satisfaction can be accomplished by adding a cultural touch to tourist attractions, improving the local cultural heritage performance, and improving infrastructure and accommodation to facilitate tourist access. Policy recommendations and suggestions are required to improve Agritourism.